2011
DOI: 10.1007/s10459-010-9265-0
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing virtual patients in clinical learning: a phenomenological study

Abstract: Computerised virtual patients (VPs) are increasingly being used in medical education. With more use of this technology, there is a need to increase the knowledge of students' experiences with VPs. The aim of the study was to elicit the nature of virtual patients in a clinical setting, taking the students' experience as a point of departure. Thirty-one students used VPs as a mandatory part of an early clinical rotation in rheumatology. Using the qualitative approach of phenomenology, we interviewed these studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 36 publications
3
46
1
2
Order By: Relevance
“…• Studies regarding its place in the curriculum Studies have shown that designs that are associated with seminars, courses and corresponding tests [40], that are balanced [41] and appropriately integrated into the curriculum [42] all motivate students. Edelbring emphasized the importance of assessing VP-based activities not as separate phenomena but as an integrated whole together with other educational activities [42].…”
Section: Vp Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Studies regarding its place in the curriculum Studies have shown that designs that are associated with seminars, courses and corresponding tests [40], that are balanced [41] and appropriately integrated into the curriculum [42] all motivate students. Edelbring emphasized the importance of assessing VP-based activities not as separate phenomena but as an integrated whole together with other educational activities [42].…”
Section: Vp Designsmentioning
confidence: 99%
“…Edelbring emphasized the importance of assessing VP-based activities not as separate phenomena but as an integrated whole together with other educational activities [42].…”
Section: Vp Designsmentioning
confidence: 99%
“…In a study by Edelbring et al [14], students reported a perceived benefit to their clinical reasoning skills from working on VP cases with a partner and discussing their patient management approaches. Furthermore, motivation has been identified as being a dependent variable influenced by autonomy [15], which is also a necessary skill when working on VP cases.…”
Section: Introductionmentioning
confidence: 99%
“…The use of phenomenology as both a method and theoretical framework within medical research broadly and post-graduate medical residency specifically, is modest at best. However, there do exist at least three instances of phenomenology being used specifically to investigate topics related to medical education, including conceptions of being a health advocate (Dharamsi et al, 2010;Edelbring, Dastmalchi, Hult, Lundberg, & Owe Dahlgren, 2011;Tavakol, Dennick, & Tavakol, 2012), and with palliative medicine (Mak & Elwyn, 2003). Since this study is grounded within a hermeneutic phenomenological tradition, it will be a novel addition to a number of areas of literature, including qualitative health research, emergency medicine, post-graduate medical education and workplace learning.…”
Section: A Phenomenological Perspective For Studying Learning In Healmentioning
confidence: 99%
“…There are opportunities where further training could incorporate Lowenstein's (1994) research on the 'curiosity gap' whereby Residents participate in simulations prior to the didactic sessions such that they are more engaged with the material presented. Nevertheless, given the increased use of simulation training within the context of PGME, this area warrants further research, especially when related to increasing the fidelity of simulations (Edelbring et al, 2011;Teteris, Fraser, Wright & McLaughlin, 2012). This would benefit both the learners, but also by extension the patients.…”
Section: Structured Learning Experiences: Informal In Practicementioning
confidence: 99%